Rote-Meto Comparative Dictionary - Edwards, Owen (Asia-Pacific Linguistics, 2021)
This comparative dictionary provides a bottom-up reconstruction of the Rote‑Meto languages of western Timor. Rote-Meto is one low-level Austronesian subgroup of eastern Indonesia/Timor-Leste. It contains 1,174 reconstructions to Proto-Rote-Meto (or a lower node) with supporting evidence from the modern Rote-Meto languages. These reconstructions are accompanied by information on how they relate to forms in other languages including Proto‑Malayo‑Polynesian etyma (where known) and/or out-comparisons to putative cognates in other languages of the region. The dictionary also contains two finder-lists: English to Rote-Meto, and Austronesian reconstructions with Rote-Meto reflexes. The dictionary is preceded by three introductory chapters. The first chapter contains a guide to using the dictionary as well as discussion of the data sources. The second chapter provides a short synchronic overview of the Rote-Meto langauges. The third chapter discusses the historical background of Rote-Meto. This includes sound correspondences, the internal subgrouping of the Rote-Meto family, and the position of Rote-Meto within Malayo-Polynesian more broadly.